r2=-90

Take the square root of both sides of the equation to eliminate the exponent on the left side.

r=±-90

Simplify the right side of the equation.

Rewrite -90 as -1(90).

r=±-1⋅90

Rewrite -1(90) as -1⋅90.

r=±-1⋅90

Rewrite -1 as i.

r=±i⋅90

Rewrite 90 as 32⋅10.

Factor 9 out of 90.

r=±i⋅9(10)

Rewrite 9 as 32.

r=±i⋅32⋅10

r=±i⋅32⋅10

Pull terms out from under the radical.

r=±i⋅(310)

Move 3 to the left of i.

r=±3i10

r=±3i10

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

r=3i10

Next, use the negative value of the ± to find the second solution.

r=-3i10

The complete solution is the result of both the positive and negative portions of the solution.

r=3i10,-3i10

r=3i10,-3i10

r=3i10,-3i10

Solve for r r^2=-90